The Virtualization of Organisations From The Perspective of The Dimensions of Organisational Change: A Conceptual Analysis. - Ay, Muammer (Electronic Turkish Studies)
Rapid advances in information and communication technologies have profoundly transformed the structure of organizations, their business processes, and the ways in which they interact with stakeholders— citizens or customers. As a result of this transformation, the virtual presence of organizations operating in sectors that constitute the core of contemporary social life—such as banking, healthcare, education, and retail— has been steadily increasing. This growing presence has led organizations into a new process of organizational transformation, giving rise to the phenomenon of "organizational virtualization." The purpose of this study is to identify the key factors driving the virtualization of organizations, to analyze this phenomenon through the lens of the dimensions of organizational change (planning, magnitude, and continuity), and to develop a conceptual framework for understanding organizational virtualization. Designed as a qualitative study, the research is based on a comprehensive literature review and conceptual analysis. The findings indicate that virtualization may emerge in both planned and unplanned forms; while in the private sector it is mainly driven by market competition, customer expectations, and technological innovation, in the public sector it is primarily shaped by policy directives and regulatory pressures. The study further reveals that virtualization in the public sector tends to represent a more institutionalized and continuous transformation, whereas in the private sector it occurs in a more reactive and discontinuous manner. Key driving forces behind organizational virtualization include information and communication technologies, artificial intelligence, customer demands, the Covid-19 pandemic, and changing competitive conditions. While virtualization offers organizations various advantages—such as enhanced reputation, increased brand visibility, greater transparency, reduced bureaucracy, and lower costs—it also introduces challenges related to control, efficiency, and data security. By integrating the concepts of organizational change and organizational virtualization, this study positions virtualization as a multidimensional manifestation of organizational change and argues that, in the digital age, virtualization has become a strategic necessity for sustaining organizational existence.